The Role of Parents in Reducing the Risk of Mental Health Disorders in Adolescents: A Scoping Review - Anggela Pradiva Putri; Tris Eryando (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Adolescent mental health has become a global issue, especially with the rising cases of depression and anxiety following the COVID-19 pandemic. According to WHO data (2023), approximately 20% of adolescents worldwide experience mental health disorders, with the prevalence of mental disorders in Asia reaching 28% in 2022. In Indonesia, the 2023 Indonesian Health Survey (SKI) reported that 2% of adolescents aged 15-24 suffer from depression. Social and economic factors, along with the significant role of the family, greatly influence adolescent mental health, especially in reducing the risk of mental health disorders. Objective : This study aims to conduct a scoping review of adolescent mental health disorders and explore the role of parents in reducing the risk of these disorders. The primary focus is on how parenting practices influence adolescent mental health. Research Methods/ Implementation Methods : A scoping review method was employed to map relevant literature on adolescent mental health disorders globally. Literature searches were conducted through databases such as ProQuest, Sage Journal, PubMed, Scopus, and Science Direct, selecting articles published between 2014 and 2024. Results : The findings indicate that strong emotional attachment with parents and positive parenting practices can help reduce anxiety and enhance adolescents' emotional well-being. Parenting that involves open communication, emotional support, and acceptance of the child's feelings has proven effective in reducing the risk of mental health disorders in adolescents. Conclusion/Lesson Learned : The role of parents in providing consistent emotional support is crucial for adolescent mental health. Parental involvement in fostering a strong emotional connection can reduce anxiety, enhance emotional well-being, and play a significant role in preventing mental health disorders.